Beat the Cheats. - Euchner, Charles (American (19328117))
As students increasingly use technology to cheat on school papers, educators are struggling to find effective means of thwarting them. Turnitin.com, a program that searches papers and websites for matching content, is one of the most popular anti-cheating programs on U.S. campuses. However, Turnitin.com has come under fire from students at McLean High School, Virginia, for violating copyright and privacy rights. In addition, some educators fear that using such technology may foster an atmosphere of mistrust on campuses. Instead, some institutions have introduced nontechnological measures, such as honor codes and grades that indicate cheating.